DIFFERENCES OF JIGSAW LEARNING METHOD AND LECTURE METHOD TO STUDYING RESULT OF MIDWIFERY BASE SKILL IN POLTEKKES SURAKARTA - Elwitri Silvia; Supiati .; Kuswati . (STIKES DUTAGAMA KLATEN, 2014)
Background: Based on data in Academic Administration of Poltekkes Surakarta, there are 17% first semester students in 2012/2013 get theory score midwifery base skill lower than 68. One of factors that influence studying result is learning method. During this time, learning method that is often used is lecture method. Jigsaw is cooperative learning method that can improve students studying result. Objective: This research is aim to know differences of jigsaw learning method dan lecture method to studying result of midwifery base skill in Poltekkes Surakarta.Research Methods: Type of research is quasy experiment with expansion of design pretest-posttest with control group. The technique of interpretation sampling is cluster sampling with population is all students in first semester Midwifery DIII Study Program of Poltekkes Surakarta that is consist of 3 classes and it was take 2 classes for sample which amounts to 75 students. This research use one of midwifery base skill subject, that is principle of infection prevention. Result: Univariat analysis indicate that pretest average with jigsaw method and lecture method are 45,27 and 45,39 while posttest average of jigsaw method is higher than lecture method, that is 78,83>66,67. Based on analysis unpair t-test was got that p<0,05 (0,000<0,05), it’s mean null hypothesis is rejected. Conclusion: There are differences jigsaw learning method dan lecture method to the studying result of midwifery base skill in Poltekkes Surakarta.